ETMR-03. THE ROLE OF FOXR2 IN PEDIATRIC BRAIN CANCER. (4th December 2020) - Schmitt-Hoffner, Felix; van Rijn, Sjoerd; Hübner, Jens-Martin; Lambo, Sander; Mauermann, Monika; Mack, Norman; Schwalm, Benjamin; Pfister, Stefan; Kool, Marcel
Abstract: Forkhead Box R2 (FOXR2) is a transcription factor of the Forkhead Box family that has been correlated with tumorigenesis, aberrant cell growth or tumor progression. Expression of FOXR2 in pediatric brain tumors is, besides in subsets of medullo-, pineo- and glioblastoma, primarily present in CNS neuroblastoma with FOXR2 activation (CNS NB-FOXR2), a novel entity that we in 2016 identified from the former class of primitive neuroectodermal tumors of the central nervous system (CNS-PNET). Analyzing CNS-NB-FOXR2 tumors we found that FOXR2 mRNA is expressed in an anti-correlative manner compared to the proto-oncogenes MYC and MYCN . With immunoprecipitation analyses we show that FOXR2 binds to MYC and MYCN and is thereby stabilizing these proteins. These observations on the interaction and the anti-correlative manner suggest that FOXR2 and MYC(N) may drive tumor formation in a molecularly similar fashion. To investigate this further we stably expressed FOXR2, MYCN and MYC and a combination of FOXR2 with MYC ( N ) in human neural stem cells (hNSC) and injected these in the striatum of NSG mice. We could show that hNSC itself do not from a tumor, whereas the expression of FOXR2 and/or MYC ( N ) in hNSC results in tumorigenesis. Tumors expressing both, FOXR2 and MYC(N ) were growing faster than tumors with FOXR2 alone. In addition, tumors are currently being analyzed by ChIP-sequencing for FOXR2, MYC, and MYCN, to better understand the mechanisms how FOXR2 drives tumor formation compared to its interaction partners MYC and MYCN.